A new parthenogenetic bagworm Reisseronia imielinella sp. nov. from Poland (Lepidoptera, Psychidae) - Malkiewicz, Adam; Sobczyk, Thomas; Larysz, Adam (Zootaxa, 2013)
Reisseronia imielinella sp. nov. is described from the province of Upper Silesia (Śląskie voivodship) in southern Poland and compared with its closest parthenogenetic relative Reisseronia gertrudae Sieder, 1962. The new species is well characterized by the structures of the female antennae and legs. The breeding of an F1 generation was successful and is described, as is the species’ habitat and life history.